SIGI PENGGUNAAN ALAT EVALUASI MATA PELAJARAN EKONOMI MATERI AKUNTANSI KELAS XI DI SMA NEGERI 1 MANYAR - NUR ASTUTIK (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2013)
Evaluation is an activity or process of measuring the achievement of education goals. Evaluation tool is a tool used to measure the achievement of learning objectives. This study aims to determine the type of evaluation tools used and the reasons, feasibility evaluation and student response tools in the implementation of accounting economic evaluation in class XI SMA Negeri 1 Manyar. This study was using descriptive study. The population in this study were all students of class XI IPS totaling 108 students, while the sample is class XI IPS 1 the 36 students were taken by random sampling technique. The data were collected through interview, documentation, and questionnaire.The results of the study show that (1) the evaluation tool used was are spons item because for students to express them selves and multiple choice more effectiv as a training computer sheets. (2) From the review of an expert evaluation tool used is said to be worth having a percentage of 90%. (3) And there sponse of the students in a positive evaluation by the total percentage of 21% strongly agree and 63% disagree. Keywords: tool, evaluation, economics, accounting, SMA